2022
DOI: 10.1101/2022.01.18.21266111
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 induces human endogenous retrovirus type W envelope protein expression in blood lymphocytes and in tissues of COVID-19 patients

Abstract: Patients with COVID-19 may develop abnormal inflammatory response and lymphopenia, followed in some cases by delayed-onset syndromes, often long-lasting after the initial SARS-CoV-2 infection. As viral infections may activate human endogenous retroviral elements (HERV), we studied the effect of SARS-CoV-2 on HERV-W and HERV-K envelope (ENV) expression, known to be involved in immunological and neurological pathogenesis of human diseases. Our results have showed that the exposure to SARS-CoV-2 virus activates e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 88 publications
(122 reference statements)
0
11
0
Order By: Relevance
“…Research relating HERVs to COVID-19 is ongoing and until now, accumulated data indicate differential expression of some HERV families during the acute phase of the disease, generally associated with enhancement of inflammatory processes ( 136 , 137 ). It was initially described that the envelope genes from HERV-W and HERV-K were highly expressed in peripheral blood mononuclear cells (PBMC) from healthy individuals exposed to SARS-CoV-2 in vitro , but only the HERV-W-env protein was synthesized.…”
Section: Hervs Expression In Diseasesmentioning
confidence: 99%
“…Research relating HERVs to COVID-19 is ongoing and until now, accumulated data indicate differential expression of some HERV families during the acute phase of the disease, generally associated with enhancement of inflammatory processes ( 136 , 137 ). It was initially described that the envelope genes from HERV-W and HERV-K were highly expressed in peripheral blood mononuclear cells (PBMC) from healthy individuals exposed to SARS-CoV-2 in vitro , but only the HERV-W-env protein was synthesized.…”
Section: Hervs Expression In Diseasesmentioning
confidence: 99%
“…FCS was reported to activate HERVs, primarily type W and K, triggering not only cell-cell fusion but also hyperinflammatory responses and dysfunctional proteostasis [114][115][116][117]. HERVs are viral fossils embedded in human DNA that can be "awakened" by the infection with exogenous viruses, cancer, or neuropsychiatric conditions [118][119][120].…”
Section: Hervsmentioning
confidence: 99%
“…Several studies demonstrated that SARS-CoV-2 can activate HERV-W, an ancestral gene that encodes for the physiological placental fusogen syncytin-1 responsible for the merger of trophoblasts during the early pregnancy [114,115]. This suggests that the reproductive post-vaccine events may be triggered by the FCS pathology.…”
Section: Hervsmentioning
confidence: 99%
“…FCS was reported to activate HERVs, primarily type W and K, triggering not only cell-cell fusion but also hyperinflammatory responses and dysfunctional proteostasis [112][113][114][115]. HERVs are viral fossils embedded in human DNA that can be "awakened" by the infection with exogenous viruses, cancer, or neuropsychiatric conditions [116][117][118].…”
Section: Hervsmentioning
confidence: 99%
“…Several studies demonstrated that SARS-CoV-2 can activate HERV-W, an ancestral gene that encodes for the physiological placental fusogen syncytin-1 responsible for the merger of trophoblasts during the early pregnancy [112,113]. This suggests that the reproductive post-vaccine events may be triggered by the FCS pathology.…”
Section: Hervsmentioning
confidence: 99%